Indirect regulation of TFPI-2 expression by miR-494 in breast cancer cells - Andresen, Marianne S. (Sci Rep, 2020)
TFPI-2 has been shown to be involved in breast cancer pathogenesis by inhibiting extracellular matrix degradation, and low levels are associated with disease progression. As microRNA-494 (miR-494) protects against breast cancer progression, we investigated whether miR-494 is involved in the regulation of TFPI-2 in MCF-7 breast cancer cells. TFPI-2 mRNA and protein levels increased after transfection with miR-494 mimic, and TFPI-2 mRNA and miR-494 levels correlated positively in tumors from breast cancer patients. No specific binding sites for miR-494 in the 3′-untranslated region (UTR) of TFPI2 were identified; however, miR-494 was predicted in silico to bind 3′-UTR of the transcription factors AHR and ELF-1, which have potential binding sites in the TFPI2 promoter. ELF-1 mRNA was downregulated whereas AHR mRNA levels were upregulated after transfection with miR-494 mimic. Knockdown of ELF-1 and AHR increased and reduced TFPI-2 mRNA levels, respectively. Increased luciferase activity was seen when TFPI-2 promoter constructs containing the potential AHR or ELF-1 binding sites were co-transfected with miR-494 mimic. In conclusion, TFPI-2 mRNA levels were upregulated by miR-494 in MCF-7 breast cancer cells most likely by an indirect association where miR-494 targeted the transcription factors AHR and ELF-1. This association was supported in a breast cancer cohort.